The Effect of Political Connection on Tax Evasion: Post-Revolutionary Evidence from Tunisian Firms - Chakroun, Raida; Khemir, Azza (Asian Journal of Empirical Research, 2020)
In this study, we examine the effect of political connection on tax evasion in the Tunisian context. We use a sample of 72 Tunisian firms observed from 2012 to 2015. To measure firms’ political connections through their board of directors, we manually collected a wide-ranging data set from various sources. To measure tax evasion we relied on a fundamental proxy: the effective tax rate (ETR). The findings show that politically connected firms are more likely to avoid taxes via the practices of tax evasion than non-connected firms. Thus, directors who have former political position tend to favor the tax evasion. The results may be useful for investors in their process of evaluation of benefits and risks associated with their investment and also for tax authorities in the establishment of their plans of enforcement activities. To the best of our knowledge, until now this is the first study to investigate the effect of political connection on tax evasion for Tunisian firms.